The Effects of DNA Repair Pathway Engineering on CRISPR-Mediated Genome Editing in Neuronal Cells - Alabudeeb, Fatimah; Justus Liebig University Giessen (My University, 2025)
Inherited retinal dystrophies are a group of genetically and clinically heterogeneous disorders that vary in their clinical presentation and progression, possibly leading to blindness. So far, about 332 genes, most expressed in photoreceptors, have been identified to be associated with these diseases. The relatively new genome editing field, particularly CRISPR-Cas9 mediated genome editing technology, which introduces DNA double-strand breaks (DSBs) that are subsequently repaired by the cells' repair systems, has recently drawn much attention. The major repair pathways are non-homologous end-joining (NHEJ) and homology-directed repair (HDR). One of the main obstacles to its application in the retina is the limited knowledge of DNA repair in photoreceptors. This work aims to analyze the DNA repair mechanisms, improve CRISPR Cas9 genome editing efficacy by modulating and engineering the DNA repair pathways in mature neurons using the human inducible Neurogenin iPS (iNGN) cell line, and validate it as an in vitro model system. These cells are human-induced pluripotent stem cells that differentiate into mature neurons within 4 days. In addition, the iNGN TET3KO cell line was also investigated to determine the impact of the TET3 protein at various differentiation stages. To achieve this, the iNGN cell lines and a control cell line, HEK293T cells, were transfected with BRET reporter assay plasmid using Cas9 and the inducible Cas systems (iCas). Promoter optimizations were done by replacing the CMV promoter, which can be silenced and suppressed in certain cell types, with a sustained EF1α promoter. Applying the Cas9 system, iNGN WT and iNGN TET3KO cells were tested throughout the differentiation process. Moreover, the modifications of PARP1 protein levels using PARP1 overexpression or knockout plasmids were necessary to study its influence on the DNA repair pathways of different cell lines. The BRET reporter assay was the primary quantitative technique used. The results showed decreased frameshift rates for the undifferentiated iNGN using the iCas system compared to the Cas9 system, and along with failure to use its timing control advantage, the Cas9 system was mainly used for the remaining experiments. The undifferentiated iNGN TET3KO cells' frameshift rates, as well as at the beginning of differentiation, were significantly higher than iNGN WT ones. Furthermore, the frameshift rate results of the TET3KO overexpressed cells resembled those of iNGN WT cells. After PARP1 modulation, the frameshift rates of PARP1 downregulation were greater throughout the differentiation process of the iNGNs, regardless of the HDR template addition. Interestingly, the results of the iNGN TET3KO cells were higher than those of the WT cells. For future assessment, the generation and application of iNGNs TLR3 cell lines is essential to verify the results obtained using the BRET reporter assay at the genomic level.
Keywords: ddc:610